The impact of decentralization of health services at the municipal level on health outcomes: evidence from China - Cui, Feng; Wang, Shanshan (Frontiers in Public Health, 2024)
The impact of decentralization of health services at the municipal level on health outcomes: evidence from China Abstract：Objectives: Under the system of health decentralization, there are differences in the level of expenditure decentralization at different levels of government, and their impact on residents' health may also be different. This paper is one of the first to evaluate the effect of decentralization of health services at the municipal level from a multi-dimensional health perspective. Data and Methods: This paper uses the data of expenditure decentralization of health services at the municipal level to match the panel data from the China Household Panel Survey (CFPS) from 2010 to 2018, and uses the logit model, ordered logit model and two-way fixed effects model to empirically analyze the impact of health decentralization at the municipal level on health outcomes. Results: Based on the perspective of multi-dimensional health, from the three aspects of physical health, depression status and cognitive ability, the six sub-indicators of self-rated health, BMI standards, depression scores (summation method), depression scores (factor method), phrase test scores and mathematics test scores are discussed separately. The results show that the decentralization of health services at the municipal level has a significant promotion effect on the multi-dimensional health of residents. Conclusion: The decentralization of health services at the municipal level has important theoretical significance for promoting the reasonable division of medical and health powers and expenditure responsibilities between provincial and municipal governments, improving the efficiency of health expenditure funds, and establishing a fiscal system that matches financial resources.